2022
DOI: 10.3389/fneur.2022.765795
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy for the Treatment of Carotid Near-Occlusion With Recurrent Symptoms

Abstract: ObjectiveReport our preliminary experience of carotid endarterectomy (CEA) for the treatment of carotid near-occlusion (CNO) with recurrent symptoms.Materials and MethodsRetrospectively analyze the demographics, treatment detail, and outcomes data of 122 patients with CNO from 2014 to 2020. According to whether distal full collapse exists, patients were classified into the full collapse group and the non-full collapse group. The incidence of death, myocardial infarction, stroke, and other variables were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…Consistent with previous studies, a higher BP and carotid NO were found to be clinical risk factors for cerebral hyperperfusion after carotid revascularization 2,30 . An analysis of 51,001 CEA procedures used an overall model including preoperative, operative, and postoperative clinical variables to predict CHS and the AUC was 0.785, which was similar with the BP + NO model 2 .…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with previous studies, a higher BP and carotid NO were found to be clinical risk factors for cerebral hyperperfusion after carotid revascularization 2,30 . An analysis of 51,001 CEA procedures used an overall model including preoperative, operative, and postoperative clinical variables to predict CHS and the AUC was 0.785, which was similar with the BP + NO model 2 .…”
Section: Discussionsupporting
confidence: 85%
“…The same study concluded that CEA outcomes for CNO patients with recurrent symptoms were not worse than those described in historical control groups. 15 In our study, postoperative TIA, ipsilateral ischemic stroke, and mortality rates, which were the study’s primary endpoints, were similar among our patient groups. We have no data on CNO patients, followed by BMT.…”
Section: Discussionsupporting
confidence: 60%
“… 13 In another recent study of 122 CNO patients, the success rate of the procedure was reported to be 100%, and the perioperative surgical risk in CNO patients was similar to that of non-CNO patients. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with distal ICA collapse associated with cervical ICA stenosis have difficulty in shunt insertion during CEA due to the narrow distal ICA. [ 14 ] In addition, it has been reported that CAS failed due to difficulty in system delivery, causing dissection and spasm. [ 1 , 10 , 12 ] Therefore, device induction into a collapsed ICA should be done with caution.…”
Section: Discussionmentioning
confidence: 99%